2019
DOI: 10.1111/pbi.13057
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome A signal transduction 1 and CONSTANSLIKE 13 coordinately orchestrate shoot branching and flowering in leafy Brassica juncea

Abstract: Summary Branching is a major determinant of crop yield, and enables vigorous shoot growth and the production of a dense canopy. Phytochrome A signal transduction 1 ( PAT 1) positively regulates phytochrome A signal transduction in response to light, but its effects on branching remain unknown. In this study, we mapped PAT 1 , and revealed a previously unknown role related to branching and flowering in leafy Brassica juncea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Several QTL have been mapped in the Indian and East European gene pool lines [38][39][40][41][42][43][44] . The Chinese vegetable types like Tumida constitute another divergent gene pool 5 that contains potentially useful traits like serrated leaves, basal branching 45 , and stem strength.…”
Section: Discussionmentioning
confidence: 99%
“…Several QTL have been mapped in the Indian and East European gene pool lines [38][39][40][41][42][43][44] . The Chinese vegetable types like Tumida constitute another divergent gene pool 5 that contains potentially useful traits like serrated leaves, basal branching 45 , and stem strength.…”
Section: Discussionmentioning
confidence: 99%
“…It can be easily applied in many species to study gene function either individually or on a large scale. pTY-S is a newly developed VIGS vector, which contains the entire genome of TYMV, and the 35S CAMV promoter and terminator (Pflieger et al, 2008; Huang et al, 2018a,b; Muntha et al, 2018). It possesses a strong infection ability, produces liable and robust VIGS effects that lasts throughout the plant life (Pflieger et al, 2008), and has been successfully applied in Chinese cabbage (Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although improved broccoli F 1 hybrids typically exhibit strong apical dominance, variability in lateral side-shoot growth occurs among genotypes, typically under environmentally stressed conditions (Potters et al, 2007). In a bulk-segregant analysis of shoot branching in B. juncea , Muntha et al (2018) identified BjPAT1 and its signal integrator BjBRC1 as branching candidates. The BoPAT1 or BoBRC1 homologs did not collocate with the LT BCI identified in BolTBDH.…”
Section: Discussionmentioning
confidence: 99%
“…The homologous candidates BRC1 (Bo1g117490 and Bo5g117410) is closely related to TEOSINTE BRANCHED1 , and is a putative transcription factor involved in arresting axillary bud development and limiting axillary bud growth (Muntha et al, 2018) and was identified within Bio 5 . Additional homologous VG candidates involved in growth and growth regulation were identified ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%